A Prediction Model of Extubation Failure Risk in Preterm Infants - Cheng, Zimei; Dong, Ziwei; Zhao, Qian; Zhang, Jingling; Han, Su; Gong, Jingxian; Wang, Yang (Frontiers in Pediatrics, 2021)
Objectives: This study aimed to identify variables and develop a prediction model that could estimate extubation failure (EF) in preterm infants. Study design: We enrolled 128 neonates as a training cohort and 58 neonates as a validation cohort. They were born between 2015 and 2020, had a gestational age between 250/7 to 296/7 weeks, and had been treated with mechanical ventilation through endotracheal intubation (MVEI) because of acute respiratory distress syndrome. In the training cohort, we performed univariate logistic regression analysis along with stepwise discriminant analysis to identify EF predictors. A monogram based on five predictors was built. The concordance index and calibration plot were used to assess the efficiency of the nomogram in the training and validation cohorts. Results: The results of this study identified a 5-minute Apgar score, early-onset sepsis, hemoglobin before extubation, pH before extubation, and caffeine administration as independent risk factors that could be combined for accurate prediction of EF. The EF nomogram was created using these five predictors. The area under the receiver operator characteristic curve was 0.824 (95% confidence interval 0.748-0.900). The concordance index in the training and validation cohorts was 0.824 and 0.797, respectively. The calibration plots showed high coherence between the predicted probability of EF and actual observation. Conclusions: This EF nomogram was a useful model for the precise prediction of EF risk in preterm infants who were between 250/7- 296/7 weeks’ gestational age and treated with MVEI because of acute respiratory distress syndrome.